Juvenıle polyposıs colı wıth atypıcal features - Küllü, Sevgi; Kalaycı, Cem; Söylemezoğlu, Figen; Tözün, Nurdan; Ulusoy, Nefise B. (My University, 1999)
A 22-year-old woman was found to have 25 polyps involving the rectum and the entire colon. Pathologic examination revealed numerous polyps that were predominantly of juvenile type with hyperplastic, adenomatous, villous and tubulovillous features in addition to a villous adenoma. These observations emphasize the relationship between these polyps and the neoplastic potential of juvenile polyposis. Additionally, this is the first case report of juvenile polyposis in association with cervical rib.
Keywords: Juvenile polyposis, Adenomatous polyps, Hyperplastic polyp.